4D.10: CHANGES IN PWV IN PREVIOUSLY UNTREATED MILD HYPERTENSIVES ARE RELATED TO REDUCTION OF BLOOD PRESSURE BY TREATMENT. (June 2015) - Rodilla Sala, E.; Millasseau, S.; Escrivá, M.; García, J.; Costa, J.A.; Pascual, J.M.
Abstract : Objective: Changes in target organ lesions, even beyond reduction of blood pressure, have been shown to have predictive value. Destiffening of arterial damage seems to be possible but the mechanisms are still elusive. We report changes in pulse wave velocity (PWV) after one year of treatment in new diagnosed previously untreated, hypertensive patients. Design and method: We included in this longitudinal study 356 consecutive, never-treated patients with suspected hypertension. After standard clinical assessment, including ambulatory blood pressure monitoring (ABPM), pulse wave analysis and PWV (Sphygmocor®, AtcorMedical), 231 showed elevated office and/or ambulatory blood pressure (BP) and received monotherapy treatment accordingly. 125 patients who showed to be normotensive, served as control group. Clinical assessment was repeated after a median of 1.1 years in the whole cohort. PWV was adjusted to BP. Results: In the whole group, 179 patients were female (50.3%), mean age was 48.8 ± 12years. The hypertensive diagnosed group tended to be older (50 vs. 46 years, p < 0, 001) and had higher PWV even after mean BP adjustment (8.6 ± 2.0 vs. 8.0 ± 1.4 m/s, p < 0.001), higher baseline office, ambulatory and central BP (145/86, 136/86 and 138/87 mmHg vs. 125/75, 120/76 and 120/79, respectively, p < 0, 001). After 1 year of treatment, BP was significantly improved only in the hypertensive group (follow-up office, ambulatory and central BP 128/75, 124/78, 121/79 mmHg, pintragroup < 0.001) and remained constant in the control group (126/74, 120/76, 120/80, pintragroup = ns). The reduction of central and peripheral systolic BP in the hypertensive group was of the same magnitude (−17 vs −17 mmHg, p = ns). PWV was significantly reduced in both groups even after BP adjustment, at follow-up they were similar between groups (7.8 vs. 7.7, p = ns). The reduction of adjusted PWV was significantly higher in the hypertensive group (Delta = 0.86 vs. 0, 20 m/s, p = 0.001). There was no differential effect in PWV reduction depending on antihypertensive class, except for patients treated with nebivolol. Conclusions: Blood pressure reduction in newly diagnosed stage 1 hypertensive patients improves PWV within a year of treatment, confirming that rapid tight control of BP is important even in mild hypertensives. Of note, arterial destiffening seems to go beyond BP reductions.